Health Communication Strategies via TikTok for the Prevention of Eating Disorders - Rando-Cueto, Dolores; De-las-Heras-Pedrosa, Carlos; Paniagua-Rojano, Francisco Javier (MDPI, 2023)
Patient assistance with severe eating disorders (EDs) is covered in hospital institutions by the specialized service offered. To a lesser extent, these types of pathologies are treated from health prevention, and there are hardly any experiences of health promotion in EDs through social networks. The main objective of this study was to evaluate the effectiveness of the messages about ED spread on TikTok, particularly those disseminated by international hospitals. For this, a systematic review of the scientific literature has been conducted, and the analytic tools Fanpagekarma and analisa.io have been used to analyse TikTok accounts of hospital entities and an intentional sample of different tiktokers with EDs or in recovery and people who show themselves as valid advisers in this matter, as well as their followers, respectively. Among the results obtained (due to volume and lack of transparency), the strategies of those who participate in TikTok to promote unhealthy eating habits are striking, as well as the amount of content presented against the spread of EDs that has the opposite effect on receivers. This study highlights the influence of TikTok on people affected by an eating disorder or are vulnerable to suffer from it and advocates for the spread of communication proposals via this social network that are supervised or led by health specialists who validate the content of the messages from a hospital environment to prevent such disorders. The definition of lines of action in communication by health institutions in this sense is shown to be necessary to prevent the appearance of EDs or to slow down their growth.
Keywords: Redes sociales; Anorexia - Prevención; Conducta alimentaria - Trastornos - Prevención; Riesgos para la salud - Comunicación; TikTok; Eating disorders; Anorexia; Health communication; Social media